CBX2 Inhibits Neurite Development by Regulating Neuron-Specific Genes Expression - Gu, Xi; Wang, Xuemin; Su, Dazhuang; Su, Xiaohong; Lin, Lifang; Li, Shuji; Wu, Qiaoqi; Liu, Shuhu; Zhang, Peidong; Zhu, Xinhong; Jiang, Xiaodan (Frontiers in Molecular Neuroscience, 2018)
Polycomb group (PcG) proteins regulate the epigenetic status of transcription regulatory states during development. Progression from pluripotency to differentiation requires the sequential activation and repression of different PcG target genes, however, the relationship between early patterning signals, PcG expression, and the development of the Central nervous system (CNS) is still unclear. Using various models of neuronal differentiation, we provide evidence that CBX2 is a negative regulator of neuronal differentiation. Knock-down of CBX2 expression promotes neurite development, while overexpression of CBX2 inhibits neurite development. Further, we found that CBX2 is a direct target gene of miR-124. During neuronal differentiation, CBX2 was decreased while miR-124 was increased. Mechanistically, CBX2 directly interacts with the promoter region of several neuro-associated genes and regulates their expression. We found that the neuron-specific GAP-43 gene could contribute to the stimulating effect on neurite development associated with inhibition of CBX2.